Fluidattenuated inversionrecovery SSFP imaging - Bangerter,NK; Hargreaves,BA; Gold,GE; Stucker,DT; Nishimura,DG (Journal of Magnetic Resonance Imaging, 2006)
Abstract Purpose To describe and evaluate a fast, fluidsuppressed 2D multislice steadystate free precession (SSFP) neuroimaging sequence. Materials and Methods We developed a fast fluidattenuated inversionrecovery SSFP sequence for use in neuroimaging. The inversion time (TI) was optimized to yield good cerebrospinal fluid (CSF) suppression while conserving white matter (WM)/lesion contrast across a broad range of flip angles. Multiple SSFP acquisitions were combined using the sumofsquares (SOS) method to maximize SNR efficiency while minimizing SSFP banding artifacts. We compared our fluidattenuated inversionrecovery (FLAIR) SSFP sequence with FLAIR fast spinecho (FSE) in both normal subjects and a volunteer with multiple sclerosis. SNR measurements were performed to ascertain the SNR efficiency of each sequence. Results Our FLAIR SSFP sequence demonstrated excellent CSF suppression and good gray matter (GM)/WM contrast. Coverage of the entire brain (5mm slices, 24cm FOV, 256 × 192 matrix) was achieved with FLAIR SSFP in less than half the scan time of a corresponding FLAIR FSE sequence with similar SNR, yielding improvements of more than 50% in SNR efficiency. Axial scans of a volunteer with multiple sclerosis show clearly visible plaques and very good visualization of brain parenchyma. Conclusion We have demonstrated the feasibility of a very fast fluidsuppressed neuroimaging technique using SSFP. J. Magn. Reson. Imaging 2006. © 2006 WileyLiss, Inc.